2016
DOI: 10.1159/000446345
|View full text |Cite
|
Sign up to set email alerts
|

Skin Care in the Tattoo Parlor: A Survey of Tattoo Artists in New York City

Abstract: To understand the role that tattooists play in providing skin care advice, we conducted an online, survey-based study of 90 licensed tattooists in New York City. The survey asked tattooists about their exposure to adverse tattoo events, advising on tattoo removal/correction, behaviors regarding preexisting skin conditions and aftercare, confidence in addressing client questions about adverse events and preexisting conditions, and prior training about skin conditions related to tattoos. Most tattooists (92.8%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…The most common short-term complications of tattoos include swelling, itching, and scabbing [ 4 ]. Other complications of tattoos include acute and chronic infections, ranging from local responses to systemic chronic infections, and allergic reactions, such as contact dermatitis from ink pigments, as well as urticarial and granuloma formation [ 5 - 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most common short-term complications of tattoos include swelling, itching, and scabbing [ 4 ]. Other complications of tattoos include acute and chronic infections, ranging from local responses to systemic chronic infections, and allergic reactions, such as contact dermatitis from ink pigments, as well as urticarial and granuloma formation [ 5 - 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tattoo artists play a pivotal role in counseling patients on the aftercare and adverse effects of tattooing. A previous report showed that only 55.2% of surveyed tattoo artists either look out or point out atypical moles while tattooing [ 6 ]. Our case highlights that a close examination of tattoos can detect the development of melanoma in early stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another reason for the lack of formaldehyde-related ACD tattoo reactions may be that clients often contact the tattooist about adverse tattoo reactions instead of seeing a dermatologist. 28 In theory, formaldehyde sensitization from tattoo inks is plausible. Cutaneous sensitization develops when an antigen is recognized by dermal dendritic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Tattoo healing is usually complete after 2–3 weeks 4,5 . Unfortunately, according to a number of European surveys, immediate adverse tattoo reactions can occur in 15%–68% of cases 6 . The most frequent acute tattoo cutaneous reactions are irritation, infection, delay in healing, itching, and stinging, 3,7 which can potentially adversely affect the aesthetic appearance of the tattoo.…”
Section: Introductionmentioning
confidence: 99%